Raising the Achievements of Schoolchildren in Mountain Regions by Means of Using Local History/Lore Materials - Kobal, Vasyl; Kobal, Maryna (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article is devoted to the effectiveness of the use of local lore material in mountainous terrain schools to improve student achievement in the development of their cognitive interest. In particular, the analysis of the role of the school in the development of Ukrainian Carpathian mountain areas of education and younger generation training. Attention is drawn to the fact that during the organization of the educational process in schools of mountainous terrain ,we are to take into consideration rather high level of spirituality of Highlanders, their love for their land , traditions and customs. Therefore, during the lessons of social and humanitarian course the teacher is to use local history material that will provide development of students cognitive interest. The authors in the experimental studies process demonstrated that the organization of learning the history of Ukraine in the 5th grade should be directed to the development of cognitive interest in history. So, the children in the 5th grade will not have to study the whole history. They are to be prepared to gradually assimilate to it according to the curriculum. A critical factor in successful learning is to form cognitive interest. To make the learning process easier and more interesting the teacher must offer his/her students the curriculum material which they would not only feel, but also easily understand. The students must realize that it's not about teaching something/someone unknown, but about themselves, their parents, grandparents, great grandparents, family, region, country. Therefore, the initial training should dominate local history material, allowing the development of cognitive interest in history, lay the foundations of historical knowledge and provide increasing levels of students’ achievements. This is ensured by a parallel study of the history of the native land. The authors defined teaching and learning requirements for local lore material to be used in the process of study and presented their own examples .